Sheaves on fibered threefolds and quiver sheaves - Szendroi, B (2008)
This paper classifies a class of holomorphic D-branes, closely related to framed torsion-free sheaves, on threefolds fibered in resolved ADE surfaces over a general curve C, in terms of representations with relations of a twisted Kronheimer-Nakajima-type quiver in the category Coh(C) of coherent sheaves on C. For the local Calabi-Yau case CA1 and special choice of framing, one recovers the N = 1 ADE quiver studied by Cachazo-Katz-Vafa. © 2007 Springer-Verlag.